2022
DOI: 10.1161/circep.122.011207
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Prediction of Ventricular Arrhythmic Risk in Patients With Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: Background: The arrhythmogenic right ventricular cardiomyopathy (ARVC) risk calculator stratifies risk for incident sustained ventricular arrhythmias (VA) at the time of ARVC diagnosis. However, included risk factors change over time, and how well the ARVC risk calculator performs at follow-up is unknown. Methods: This was a retrospective analysis of patients with definite ARVC and without prior sustained VA. Risk factors for VA including age, nonsustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…ARVC is a disease with incomplete penetrance. 2 While significant progress has been made in risk stratification of patients suspect of ARVC, [30][31][32] it remains unpredictable whether or when the disease will present in an asymptomatic gene carrier. 2 As such, any future implementation of gene therapy in PKP2 pathogenic variant carriers will likely not be in an asymptomatic individual as a preventive measure, but as a therapeutic procedure for a patient with an overt disease.…”
Section: Discussionmentioning
confidence: 99%
“…ARVC is a disease with incomplete penetrance. 2 While significant progress has been made in risk stratification of patients suspect of ARVC, [30][31][32] it remains unpredictable whether or when the disease will present in an asymptomatic gene carrier. 2 As such, any future implementation of gene therapy in PKP2 pathogenic variant carriers will likely not be in an asymptomatic individual as a preventive measure, but as a therapeutic procedure for a patient with an overt disease.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this, recent data tracking ARVC patients longitudinally over time have also suggested that 5-year VA risk drops by nearly 50% between the time of initial diagnosis and 5-year follow-up. 24 , 25 It is therefore possible that enrolment of European patients later in the disease process may have contributed to their observed lower rate of VA events. Importantly, prior studies have demonstrated adequate calibration of the ARVC risk calculator in both European and North American patients, 9 , 10 and thus, these phenotypic discrepancies are accounted for during calculation of VA risk.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the high persisting arrhythmic risk within this population, as patients may receive their first appropriate ICD shock more than 10 years after ICD implantation, which is important for patient counselling concerning lifestyle and ongoing ICD indication in case of battery depletion, even without prior documentation of VA. Interestingly, even though ARVC is a progressive disease, the amount of appropriate ICD shocks seems to decline over time (figure 2), which reflects optimisation of treatment including the generous use of antiarrhythmic drugs, heart failure medication, catheter ablation, physical restriction and optimised ICD programming as previously reported. VT with a cycle length of <240 ms (>250 bpm) is described as potentially life-threatening (life-threatening ventricular arrhythmia (LTVA)) 16 17. It may be speculated that by treatment of such an episode, a life is potentially saved.…”
Section: Discussionmentioning
confidence: 99%